ANALISA PEMERIKSAAN GENU JOINT PROYEKSI ANTEROPOSTERIOR (AP) POSISI SUPINE DENGAN VARIASI PENYUDUTAN CENTRAL RAY - Dwi Laila Sukmawati; Tris Budiyono; Puput Khusniatul M; Muhammad Faik (Perhimpunan Radiografer Indonesia (PARI), 2019)
ABSTRACT The purpose of this study was to determine the different information on the greatest open joint gap with the variation of central ray angling in the genu joint examination. This type of research employed descriptive quantitative research with an experimental approach on three volunteers with pelvic thickness of 25 cm, 20 cm, and 16 cm measured from the anterior superior iliac spines (ASIS) to the examination table surface.. The results showed that the greatest open joint gap was in the genu joint Anteroposterior projection (AP) with pelvic thickness of 25 cm and 20 cm, respectively 5.21 mm and 8.74 mm at 50 cephalad central ray obstruction. The largest open joint gap in the pelvic thickness of 16 cm was 5.94 mm in the 50 caudad central ray angle.